2022
DOI: 10.1101/2022.10.24.513629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hsp47 Promotes Biogenesis of Multi-subunit Neuroreceptors in the Endoplasmic Reticulum

Abstract: Protein homeostasis (proteostasis) deficiency is recognized as a contributing factor to many neurodegenerative, neurological, and metabolic diseases. However, how the proteostasis network orchestrates the folding and assembly of multi-subunit membrane proteins is not completely understood. In this investigation, we focus on characterizing the biogenesis pathway of a multi-subunit neuroreceptor, the gamma-aminobutyric acid type A (GABAA) receptor. Previous proteomics studies identified Hsp47 (Gene: SERPINH1), a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…For FRET experiments on GABA A receptors, (1) for FRET pair samples, HEK293T cells on coverslips were transfected with α1-CFP (donor) (0.5 μg), β2-YFP (acceptor) (0.5 μg), and γ2 (0.5 μg) subunits; (2) for the donor-only samples, to determine the spectral bleed-through (SBT) parameter for the donor, HEK293T cells were transfected with α1-CFP (donor) (0.5 μg), β2 (0.5 μg), and γ2 (0.5 μg) subunits; (3) for the acceptor-only samples, to determine the SBT parameter for the acceptor, HEK293T cells were transfected with α1 (0.5 μg), β2-YFP (acceptor) (0.5 μg), and γ2 (0.5 μg) subunits. Whole-cell patch-clamp recordings in HEK293T cells showed that fluorescently tagged GABA A receptors have similar dose-response curves of GABA as compared to untagged ion channels 17 . The coverslips were mounted using fluoromount-G (VWR, catalog #: 100502-406) and sealed.…”
Section: Pixel-based Sensitized Acceptor Emission Fret Microscopymentioning
confidence: 97%
See 4 more Smart Citations
“…For FRET experiments on GABA A receptors, (1) for FRET pair samples, HEK293T cells on coverslips were transfected with α1-CFP (donor) (0.5 μg), β2-YFP (acceptor) (0.5 μg), and γ2 (0.5 μg) subunits; (2) for the donor-only samples, to determine the spectral bleed-through (SBT) parameter for the donor, HEK293T cells were transfected with α1-CFP (donor) (0.5 μg), β2 (0.5 μg), and γ2 (0.5 μg) subunits; (3) for the acceptor-only samples, to determine the SBT parameter for the acceptor, HEK293T cells were transfected with α1 (0.5 μg), β2-YFP (acceptor) (0.5 μg), and γ2 (0.5 μg) subunits. Whole-cell patch-clamp recordings in HEK293T cells showed that fluorescently tagged GABA A receptors have similar dose-response curves of GABA as compared to untagged ion channels 17 . The coverslips were mounted using fluoromount-G (VWR, catalog #: 100502-406) and sealed.…”
Section: Pixel-based Sensitized Acceptor Emission Fret Microscopymentioning
confidence: 97%
“…Presumably, binding of Hispidulin and TP003 to the α1(G251D) variant improves stability and thus enhances the assembly and forward trafficking of GABA A receptors. We used Förster resonance energy transfer (FRET) assay to quantify the subunitsubunit assembly in HEK293T cells 17 . CFP-tagged α1(G251D) and YFP-tagged β2 exhibited a FRET efficiency of 21.4 ± 1.4%; Hispidulin or TP003 treatment significantly increased the FRET efficiency to 42.5 ± 1.2% and 41.0 ± 2.1%, respectively (Fig.…”
Section: Hispidulin and Tp003 Promote Functional Surface Expression O...mentioning
confidence: 99%
See 3 more Smart Citations